2021
DOI: 10.1007/s10961-021-09896-9
|View full text |Cite
|
Sign up to set email alerts
|

Are sustainability-oriented investors different? Evidence from equity crowdfunding

Abstract: In this article, we examine how investor motives affect investment behavior in equity crowdfunding. In particular, we compare the investment behavior of sustainability-oriented with ordinary crowd investors on six leading equity crowdfunding platforms in Austria and Germany and investigate whether they suffer from a default shock that was recently identified by Dorfleitner et al. (2019). In general, we find evidence of a default shock in equity crowdfunding that occurs immediately after the event or if investo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Because we do not know the identities of the investors of the two platforms, we cannot report the extent of multihoming. Hornuf, Stenzhorn et al (2021) have recently shown that around one-quarter of investors on three equity crowdfunding platforms from the same corporate group participated in more than one platform. In our case, we consider two completely independent platforms, each of which requires registration and authentication to make investments.…”
Section: Datamentioning
confidence: 99%
“…Because we do not know the identities of the investors of the two platforms, we cannot report the extent of multihoming. Hornuf, Stenzhorn et al (2021) have recently shown that around one-quarter of investors on three equity crowdfunding platforms from the same corporate group participated in more than one platform. In our case, we consider two completely independent platforms, each of which requires registration and authentication to make investments.…”
Section: Datamentioning
confidence: 99%
“…Before ECFPs, angel investments and venture capital were the sources of financing for the initial stages of projects (Hornuf et al, 2021), today they compete with each other (Allon & Babich, 2020). Some of the most popular ECFPs worldwide are Mintos, MicroVentures, StartEngine, Broota, Dozen, and AngelList, among others.…”
Section: Equity Crowdfunding Platformsmentioning
confidence: 99%
“…Research in recent years indicates the direct impact of CSR and performance on ESG indicators, on customer satisfaction and therefore on the creation of long-term value and financial performance of each company, criteria that also influence the investors' decisions [21]. Hornuf et al [22] pointed out that companies focusing their performance mainly towards social indices in order to achieve increased consumer satisfaction end up attracting more investors. Similarly, the research by Mehta et al [23] identified a positive relationship between firms' environmental indicators and investors' willingness to invest in them in mutual funds.…”
Section: Esg Indicators and Their Association To Csr And Customer Sat...mentioning
confidence: 99%